THE SEMICONDUCTOR THERMOELECTRIC DEVICE FOR TEMPERATURE CONTROL OF COMPUTER PROCESSOR WITH USE OF MATERIALS IN THE CONDITION OF PHASE TRANSITION - H. M. Gadjiyev; D. A. Chelushkin (Вестник Дагестанского государственного технического университета: Технические науки)
The article deals with the cooling system computer processor on the based sublimation phase transitions, allowing to provide temperature control mode in a transient thermal load, which will prevent the failure of the VLSI processor.